Perlindungan Hukum Terhadap Anak dalam Upaya Pencegahan Tindak Pidana Kekerasan Seksual pada Anak - Lubis, Muhammad Ansori (Universitas Islam Sumatera Utara, 2023)
Children are often victims of sexual violence. Children who become victims of this crime continue to increase, as if the perpetrators never feel the concern that the law will ensnare with severe sanctions. In providing protection for child victims of sexual violence and providing legal assistance for child victims of sexual violence, there are still many obstacles encountered. these obstacles are both obstacles from internal factors and obstacles from external factors. The implementation of legal protection for child victims of sexual violence in reality still cannot be implemented optimally in accordance with the policies of existing laws and regulations in Indonesia. In enforcing the law in the crime of sexual violence against children, it can fulfill a sense of justice for the victim, the victim's family and the community. Based on Law Number 35 of 2014 concerning the legal protection of children in article 64 (special protection of children in conflict with the law as referred to in article 59 paragraph (2) letter b) is carried out through: humane treatment by paying attention to needs in general, separation from adults, effective provision of legal aid and other assistance, or other cruel, inhuman and degrading treatment, avoidance of the imposition of the death penalty and/or life imprisonment, avoidance of arrest, detention or imprisonment, except as a last resort and within the shortest time. provision of justice before the court. Keywords: Legal Protection, Prevention, sexual